Regeneration of seed crops and their wild relatives: Proceedings of a consultation meeting 4–7 December 1995 ICRISAT, Hyderabad, India - Engels, J.M.M.; Ramanatha Rao, R.; International Crops Research Institute for the Semi-Arid Tropics (1998)
The ex situ conservation of plant genetic resources is of vital importance to contribute to long-term global food security. Ex situ conservation consists of a series of routine operations and activities, of which many are interlinked, and all of which need proper management. Regeneration of stored germplasm seed samples is one of the key activities as it has a direct bearing on the quality of the material conserved, it requires specific knowledge and expertise and it is usually labour intensive. An average of 50 percent of current national collections are in need of regeneration and urgent action is needed to avoid much of the stored genetic diversity being lost for ever. The deliberations of this meeting resulted in a much better understanding of the complexity of the regeneration process, and generated suggestions and ideas on how to make the process more efficient and cost-effective.